Skema KKN Tematik Reguler Pemilu Dan Kebangkitan Ekonomi (Pemberdayaan Masyarakat Desa Randusongo Melalui Literasi Digital Marketing) - Zulfakar, Andi Ahmad; Diandra, Aditya Rizki; Wicaksono, Annas; Fadholah, Arno; Oktaviana, Adelia Haninditya; Aji, Dodi Setya; Shaffira, , Kiran Nathania; Sari, Meilyana Cipta; Sahara, Oktavia Putri; Ardhanaisvara, Putri Adinda; Prasetyoningsih, Nanik (Universitas Muhammadiyah Yogyakarta, 2024)
Community Service Program (KKN) Group 123 was held in Randusongo Hamlet, Donokerto, Turi District, Sleman Regency, Yogyakarta. This KKN lasted for 1 month starting on January 11, 2024 - February 11, 2024. Randusongo Hamlet has several problems with UMKM, namely regarding digital marketing problems in the context of UMKM marketing. Therefore, we held a socialization to the Randusongo hamlet community which focused on marketing procedures through online media. The method used in this activity is to provide an explanation of the use of social media, share experiences, discussions, direct practice of creating social media accounts (Tiktok, Shopee, Instagram and others), in order to make them attractive to buyers (pictures, words, prices, and others). The results show that some business people actively use social media as their promotional tool, some others use it occasionally, and the rest of the Randusongo hamlet community has never used social media marketing due to lack of technology skills. So the conclusion of this activity is that the community as UMKM actors has increased their knowledge related to their understanding of digital marketing properly. In addition, the socialization and FGD methods make it easier for the community to understand digital marketing material. The implication of this research is that UMKM actors who are the target of this socialization are able to create a good business image (branding), logo and packaging for the efficiency and effectiveness of the performance of the businesses they run. The success of this KKN program is reflected in the spirit of close cooperation between the KKN team, the hamlet head, the local community, and the campus, which shows that community service-oriented higher education can have a significant positive impact on the local community.